INCREASING ECONOMIC WELFARE OF CHURCH CONGREGATION : A CONCEPT OF EMPOWERMENT - Tongam Sihol Nababan (Jurnal Ekonomi dan Studi Pembangunan, 2017)
In our community, many structural problems unresolved well, especially in social and economic life. Seeing this reality, the Church needs to have a sensitivity and a strong commitment to encourage cooperation of some parties to empower people, especially its congregation. Congregation of the Church, especially the poor need to be raised and empowered to pursue their own welfare through economic business. One manifestation of the Church's task is to empower the community-based and to revitalize its role more focused on optimizing the institution of community economy. For that, it is important to use the Model of Empowerment of Congregation-Based Community Economic in form of business partnership. The success of congregation economic empowerment lies in the motivation and orientation of the actors themselves, where the Church is expected to seriously fight.Keywords: Church, Congregation, Community-Based Economic, Business Partnership,  Empowerment.JEL Classification: D60, I31